Trends in activity and dissolution on RuO2 under oxygen evolution conditions: particles versus well-defined extended surfaces - Roy,C; Rao,RR; Stoerzinger,KA; Hwang,J; Rossmeisl,J; Chorkendorff,I; Shao-Horn,Y; Stephens,IEL (ACS Energy Letters, 2018)
Rutile RuO2 catalysts are the most active pure metal oxides for oxygen evolution; however, they are also unstable toward dissolution. Herein, we study the catalytic activity and stability of oriented thin films of RuO2 with (111), (101), and (001) orientations, in comparison to a (110) single crystal and commercial nanoparticles. These surfaces were all tested in aqueous solutions of 0.05 M H2SO4. The initial catalyst activity ranked as follows: (001) > (101) > (111) ≈ (110). We complemented our activity data with inductively coupled plasma mass spectroscopy, to measure Ru dissolution products occurring in parallel to oxygen evolution. In contrast to earlier reports, we find that, under our experimental conditions, there is no correlation between the activity and stability.